Identifikasi Inhibitor Protease NS2B/NS3 Virus Dengue Berbasis Flavonol melalui Farmakologi Jaringan dan Penambatan Molekuler - Neni Frimayanti; Haiyul Fadhli; Mazani Febrina (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
The dengue virus still poses a serious threat to world health, and there are still few effective inhibitors that target the NS2B/NS3 protease. This study used an integrated in silico methodology to find possible anti-dengue candidates from Artocarpus heterophyllus flavonol molecules. After investigating compound–target relationships using network pharmacology, structure-based molecular docking was used to evaluate binding affinities toward the NS2B/NS3 protease (PDB ID: 2FOM), and ADME profiling was included. Compounds 6 and 9 outperformed the other ligands in the evaluation in terms of expected binding energies and stable accommodation in the active site, which included close spatial interaction with the residues of the catalytic triad (His51, Asp75, and Ser135). For the most part, their anticipated pharmacokinetic characteristics were within reasonable bounds for early-stage medication candidates. All things considered, our findings suggest that the chosen flavonols would be good places to start when developing dengue antivirals; still, further experimental testing is necessary to confirm their biological activity.